Poetizing the routine in Gohar Markosyan-Kasper’s “Penelope” - Avetisyan, Venera (Bulletin of Yerevan University H: Russian Philology, 2023)
Works of the Russian-speaking Armenian writer Gohar Markosyan-Kasper, saturated with national-cultural concepts and archetypes, nevertheless, echoes the artistic traditions of both Russian postmodern literature and world classical literature. Markosyan-Kasper’s poetic manner is characterised by the principle of coexisting paradoxes linking historical-cultural, as well as life-philosophic concepts: antiquity and modernity, mythical and mundane, ordinary and incredible. The author gives in this article observations and comments on mentioned motives in the first and central novel “Penelope”. The poetization of routine, as one of the main artistic principles, is understood in the context of the polemics around the dichotomy of life and existence in Russian literature. One of the perspectives of conceptualization of the «eternal» dichotomy of life and existence in Russian literature and culture is the so-called «Soviet metaphysics», suggesting fundamental ambiguity of reality, which, according to Alexander Genis, divides life into two interpenetrating dimensions: sacral and profane. Reality in the novel «Penelope» is played out artistically in this way, simultaneously realizing the intermediate space on which these dimensions coexist. There are many metaphors of post-Soviet aesthetics, containing motives of ambiguity and peculiar duality, modification of the principle of “estrangement” developed by Shklovsky, as well as other forms and techniques, poetizing life.